Mechanisms of immunological tolerance in central nervous system inflammatory demyelination - Mari, Elisabeth R. (Clin Exp Neuroimmunol, 2015)
Multiple sclerosis is a complex autoimmune disease of the central nervous system that results in a disruption of the balance between pro-inflammatory and anti-inflammatory signals in the immune system. Given that central nervous system inflammation can be suppressed by various immunological tolerance mechanisms, immune tolerance has become a focus of research in the attempt to induce long-lasting immune suppression of pathogenic T cells. Mechanisms underlying this tolerance induction include induction of regulatory T cell populations, anergy and the induction of tolerogenic antigen-presenting cells. The intravenous administration of encephalitogenic peptides has been shown to suppress experimental autoimmune encephalomyelitis and induce tolerance by promoting the generation of regulatory T cells and inducing apoptosis of pathogenic T cells. Safe and effective methods of inducing long-lasting immune tolerance are essential for the treatment of multiple sclerosis. By exploring tolerogenic mechanisms, new strategies can be devised to strengthen the regulatory, anti-inflammatory cell populations thereby weakening the pathogenic, pro-inflammatory cell populations.